Applications of biogeochemical models in different marine environments: a review - Ismail, Kaltham A.; Al-Shehhi, Maryam R. (Frontiers in Environmental Science, 2023)
Marine biogeochemical models are an effective tool for formulating hypothesis and gaining mechanistic understanding of how an ecosystem functions. This paper presents a comprehensive review of biogeochemical models and explores their applications in different marine ecosystems. It also assesses their performance in reproducing key biogeochemical components, such as chlorophyll-a, nutrients, carbon, and oxygen cycles. The study focuses on four distinct zones: tropical, temperate, polar/subpolar, and high nutrient low chlorophyll (HNLC). Each zone exhibits unique physical and biogeochemical characteristics, which are defined and used to evaluate the models' performance. While biogeochemical models have demonstrated the ability to simulate various ecosystem components, limitations and assumptions persist. Thus, this review addresses these limitations and discusses the challenges and future developments of biogeochemical models. Key areas for improvement involve incorporating missing components such as viruses, archaea, mixotrophs, refining parameterizations for nitrogen transformations, detritus representation, and considering the interactions of fish and zooplankton within the models.